Optimization of combined electricity generation and cooling load reduction by incorporating roof top photovoltaic module: An approach to energy consumption reduction in a hospital building - Khaza Shahriar; Md. Hasan Ali; Md.Khaled Mahmud; Mohammad Rezwan Hossain (Energy Conversion and Management: X)
In this era of renewable energy growth, PV systems are being used in buildings extensively for onsite off-grid electricity generation to reduce dependency on grid energy and hence dependency on fossil fuel. Among various PV systems of buildings, the Rooftop PV system is the most common practice. This system has combined the advantage of energy efficient design and use of renewable energy as rooftop PV system has not only the potential of electricity generation but also potential of cooling load reduction acting as passive cooling device by providing shadow on roof. In this study, performance test and optimization of rooftop solar PV system is studied considering three different PV system mountings: south facing single separate string, south facing multiple string attached system and east–west facing system. A 35.5 kWp PV system was designed considering KUET Medical Center building and was analyzed in terms of tilt angle and height of the panel from roof surface considering optimum row spacing. It was found that multiple string attached system offers the best performance in terms of electricity generation, cooling load reduction and CO2 reduction with an annual cooling load reduction of 16.6%, generation of 65.6 MWh and CO2 reduction of 32.55 tons. The optimum tilt angle for single-string, multi-string and east–west system was found 24°, 28° and 2°, respectively. In all cases, generation increases with the increase of height from roof surface. The cost analysis suggests that along with other benefits, multi-string attached system has the lowest LCOE of 6.10 BDT/kWh, shortest payback period and highest ROI compared to the other two systems. Greater generation than the electricity load suggests that incorporating PV system can make the studied building net positive energy building and the surplus electricity can be used in other buildings or supplied to grid. The results suggest that locations with higher solar exposure, benefit the from integrated rooftop PV implementation not only reduces dependence on conventional energy sources but also ensures a sustainable and uninterrupted power supply for healthcare facilities.